2007
DOI: 10.1021/jf0625353
|View full text |Cite
|
Sign up to set email alerts
|

Does Oxidation Affect the Water Functionality of Myofibrillar Proteins?

Abstract: Water-binding properties of myofibrils extracted from porcine muscle, and added hemoglobin with and without exposure to H2O2, were characterized using low-field proton NMR T2 relaxometry. The effects of pH and ionic strength in the samples were investigated as pH was adjusted to 5.4, 6.2, and 7.0 and ionic strength was adjusted to 0.29, 0.46, and 0.71 M, respectively. The formation of dityrosine as a measure of oxidative protein cross-linking revealed a significant increase in dityrosine concentrations upon H2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 41 publications
3
49
0
5
Order By: Relevance
“…Firm, deformable gels are produced with breast myofibrillar proteins, while the gels formed with red muscle myofibrillar proteins are lower in textural properties (Foegeding, Brekke Clark, & Xiong Youling, 1991). Myofibrillar proteins are important for functional properties of meat and meat products, especially water holding capacity (WHC) (Bertram et al, 2007). Producers are currently using a wide range of vegetable additives, especially soy or whey protein derivates so as to improve the functional properties of meat proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Firm, deformable gels are produced with breast myofibrillar proteins, while the gels formed with red muscle myofibrillar proteins are lower in textural properties (Foegeding, Brekke Clark, & Xiong Youling, 1991). Myofibrillar proteins are important for functional properties of meat and meat products, especially water holding capacity (WHC) (Bertram et al, 2007). Producers are currently using a wide range of vegetable additives, especially soy or whey protein derivates so as to improve the functional properties of meat proteins.…”
Section: Introductionmentioning
confidence: 99%
“…However, no significant differences in expressible moisture content were obtained between gels from oxidized washed mince added with MTGase at 0.3 and 0.6 unit/g (P>0.05). Bertram et al (2007) reported that reduced WHC of purified myofibrils upon oxidation with Hb and H 2 O 2 was found together with an increase in formation of the cross-linked oxidation product. When MTGaseat 0.6 unit/g was added, expressible moisture content of control and oxidized sample was reduced by 18.3 % and 8.2 %, respectively compared to those without MTGase addition.…”
Section: Expressible Moisturementioning
confidence: 99%
“…A oxidação proteica provoca várias alterações físico-químicas das proteínas, incluindo a destruição de aminoácidos, com diminuição da solubilidade da proteína, devido à polimerização da proteína, a perda de atividade da enzima e a digestibilidade da proteína prejudicada. Tais alterações dependem da natureza do aminoácido oxidado, da atividade enzimática, da capacidade de retenção de água e, da estrutura da miosina (ARNOLD et al, 1993;TOLDRÁ, 1998;VAN LAACK et al, 2000;XIONG, 2000;HARRIS et al, 2001;FENAILLE;TABET;GUY, 2004;KEMP et al, 2010;ROWE et al, 2004a, b;BERTRAM et al, 2007;LUND et al, 2007;OOIZUMI;XIONG, 2008 As consequências do fornecimento de β-agonistas na dieta dos animais relacionadas a maciez da carne, foi relatado por Koohmaraie et al (1996) O fornecimento de tratamentos com β-agonistas induz a uma diminuição na capacidade proteolítica da musculatura esquelética, levando a uma menor taxa de degradação proteica e consequentemente a um acréscimo no teor de proteínas de animais tratados com β-agonistas adrenérgicos. Essa capacidade proteolítica reduzida também pode influenciar durante o processo de degradação proteica post mortem, com consequente influência no "amaciamento" post mortem.…”
Section: Perfil Proteico Da Carne In Naturaunclassified